ANDROID-BASED KEKASIH EDUCATIONAL STRATEGY TO IMPROVE PREGNANT WOMEN’S LITERACY ON EXCLUSIVE BREASTFEEDING - Epti Yorita; Rina; Mariati (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Despite existing health policies and breastfeeding support programmes, the coverage of exclusive breastfeeding in several areas of Bengkulu City remains low. Contributing factors include pre-lactation feeding, cultural influences, limited knowledge and inadequate access to reliable information. Therefore, a health education strategy that provides continuous access to information for pregnant women is needed to improve literacy about exclusive breastfeeding during pregnancy, using the Android-based KEKASIH digital education programme. This quasi-experimental study involved 70 women in their third trimester of pregnancy, who were divided into two groups: an intervention group, who received exclusive breastfeeding education through the KEKASIH Android application; and a control group, who received conventional antenatal education. Exclusive breastfeeding literacy was measured before and after the intervention using a structured questionnaire. The results showed a significant increase in literacy in both groups. However, the intervention group demonstrated a greater average increase (mean difference: 4.49; p = 0.00) than the control group (mean difference: 3.91; p = 0.00). While there was no significant difference in effectiveness between the two methods based on the Mann-Whitney test (p = 0.15), digital education demonstrated a greater improvement in breastfeeding literacy. These findings suggest that the KEKASIH Android application can be used as an effective strategy for improving breastfeeding literacy among pregnant women.